Conception Timing and Autism Spectrum Disorder: Unraveling the Connection - Hamza Chaudhary, Ariba Waheed (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: The purpose of this research is to determine whether the age of conception and the frequency of autism are correlated. This research is important because it will assist parents in making healthy family planning decisions and reduce the huge financial burden associated with the health and education of these children. Objectives: To check the association of paternal and maternal factors with autism. Materials and Methods: It is a comparative cross-sectional study conducted in the Mayo Hospital Psychiatry Ward of patients with autism from ages 4 to 11. The duration of the study was 1.5 months after the approval of the synopsis. Ethical approval was taken from the IRB of KEMU. The calculation yielded a sample size of 300. A preformed questionnaire proforma was given to parents/guardians to obtain data on demographic information, pregnancy, delivery, delivery intervals, and ASD according to the ADI-R International Questionnaire. SPSS version 25 was used. The chi-square test was applied to determine the association between childbirth, demographic and other gestational factors, and ASD measured with the ADI-R scale. Children with any severity of ASD and normal school-going children were included in this study. Children with severe neurocognitive disorders were excluded. Results: A significant association between maternal age at conception and ASD was reported (p = 0.000). A significant association between paternal age at conception and ASD was also reported (p = 0.000). All other childbirth factors also had a significant association with ASD. No significant association between the birth weight of the child and ASD was reported (p = 0.064). Conclusion: The results showed a significant association of ASD with prenatal and postnatal factors and other gynaecological and obstetric factors, including the mother’s and father’s age at conception. We suggest the implementation of our findings in the clinical guidelines, family planning, and prenatal and postnatal care of the mother and the child. Keywords: Autism Spectrum Disorder, prenatal factors, postnatal factors.